Formal institutions and subjective well-being: Revisiting the cross-country evidencee - Christian Bjørnskov; Axel Dreher; Justina A.V. Fischer (ETH Zurich, KOF Swiss Economic Institute, 2008)
A long tradition in economics explores the association between the quality of formal institutions and economic performance. The literature on the relationship between such institutions and happiness is, however, rather limited. In this paper, we revisit the findings from recent cross-country studies on the institutions-happiness association. Our findings suggest that the conclusions reached by previous studies are fairly sensitive to the specific measure of happiness used. In addition, the results indicate that the welfare effects of policies may differ across phases of a country's economic development. This bears important policy implications which we discuss in the concluding section of the paper.
Keywords: I31; H10; H40; 330; Happiness; institutions; policy implications; Lebensqualität; Zufriedenheit; Institutionelle Infrastruktur; Institutionalismus; Welt